Ruminococcus gnavus ameliorates atopic dermatitis by enhancing Treg cell and metabolites in BALB/c mice - Ahn, Jae‐Rin; Lee, Seung‐Hwa; Kim, Byunghyun; Nam, Myung Hee; Ahn, Yoon Kyung; Park, Yoon Mee; Jeong, Seon‐Mi; Park, Min Jee; Song, Kun Baek; Lee, So‐Yeon; Hong, Soo‐Jong; Eigenmann, Philippe (Pediatric allergy and immunology, 2022)
Background Ruminococcus gnavus (R. gnavus) are mucin‐degrading gut bacteria that play a key role in the early colonization of the gut by serving as endogenous sources of nutrients. They can also influence immune development. We had previously reported a lower abundance of R. gnavus in infants with atopic dermatitis (AD) compared with that in healthy subjects. However, the underlying mechanisms remain unclear. In this study, we investigated the effect of orally administered R. gnavus on antibiotic treatment‐induced gut dysbiosis (and the underlying mechanism) in a mouse model of AD. Methods Four‐week‐old female BALB/C mice were administered antibiotic cocktails for 2 weeks. R. gnavus was orally administered throughout the study duration. At 6 weeks of age, AD was induced by epidermal sensitization with ovalbumin. AD phenotypes and systemic and gut immune responses were investigated. Results Orally administered R. gnavus significantly reduced AD‐associated parameters (i.e., transepidermal water loss, clinical score, total serum immunoglobulin (Ig) E level, OVA‐specific IgE level, and skin inflammation). R. gnavus treatment also resulted in significant downregulation of T helper 2–related cytokine mRNA and upregulation of interleukin (IL)‐10 and Foxp3 in the skin. The population of CD4+FOXP3+ T cells in mesenteric‐ and skin‐draining lymph nodes and butyrate levels in the cecum increased in R. gnavus‐administered AD mice. Conclusions Immune modulation by orally administered R. gnavus may alleviate AD symptoms through the enhancement of regulatory T‐cell counts and short‐chain fatty acids production in AD mice.